Au-TiO2 Nanocomposites and Efficient Photocatalytic Hydrogen Production under UV-Visible and Visible Light Illuminations: A Comparison of Different Crystalline Forms of TiO2. (4th April 2013) - Jose, Deepa; Sorensen, Christopher M.; Rayalu, Sadhana S.; Shrestha, Khadga M.; Klabunde, Kenneth J.
Abstract : Au ( 1 wt % ) / TiO 2 ( anatase or rutile or P 25 ) nanocomposites were prepared by the solvated metal atom dispersion (SMAD) method, and the as-prepared samples were characterized by diffuse reflectance UV-visible spectroscopy, powder XRD, BET surface analysis measurements, and transmission electron microscopy bright field imaging. The particle size of the embedded Au nanoparticles ranged from 1 to 10 nm. These Au/TiO2 nanocomposites were used for photocatalytic hydrogen production in the presence of a sacrificial electron donor like ethanol or methanol under UV-visible and visible light illumination. These nanocomposites showed very good photocatalytic activity toward hydrogen production under UV-visible conditions, whereas under visible light illumination, there was considerably less hydrogen produced. Au/P25 gave a hydrogen evolution rate of 1600 μ mol/h in the presence of ethanol (5 volume %) under UV-visible illumination. In the case of Au/TiO2 prepared by the SMAD method, the presence of Au nanoparticles serves two purposes: as an electron sink gathering electrons from the conduction band (CB) of TiO2 and as a reactive site for water/ethanol reduction to generate hydrogen gas. We also observed hydrogen production by water splitting in the absence of a sacrificial electron donor using Au/TiO2 nanocomposites under UV-visible illumination.